Validation of pipeline welding technology in the aspect of quality assembly connections - Wiśniewska, Mirosława; Matuszewski, Maciej (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2017)
The study investigated the possibility of using the butt welding technology of pipe joints in terms of the obtained quality of connections. Trial couplings were made and a number of non destructive and destructive tests were performed. Based on these studies it was found that each of the analyzed welding technologies was qualiÞ ed as providing the desired quality of the butt joint of the assembled pipes in terms of the quality level B according to PN-EN ISO 5817. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)